The age of low tech towards a technologically sustainable civilization - Bihouix, Philippe (Bristol University Press, 2020)
People often believe that we can overcome the profound environmental and climate crises we face by smart systems, green innovations and more recycling. However, the quest for complex technological solutions, which rely on increasingly exotic and scarce materials, makes this unlikely. A best-seller in France, this English language edition introduces readers to an alternative perspective on how we should be marshalling our resources to preserve the planet and secure our future. Bihouix skilfully goes against the grain to argue that 'high' technology will not solve global problems and envisages a different approach to build a more resilient and sustainable society.